ASPENSIA 21 ANDROID-BASED INTERACTIVE ON THE CONCEPT OF HUMAN DIGESTIVE SYSTEM - Abdul Hafiz Anshary; Bunda Halang; Noorhidayati Noorhidayati (Universitas Negeri Padang, 2022)
The concept of human digestive system is senior high school as biology material play an important role, looked by morphology, anatomy and students’ lifestyle. The 2013 curriculum includes aspects of knowledge & skills attitudes, where development of diverse teaching material such as software that can be used as instructional media, especially on the concept of human digestive system. This study aims to describe the results of developing ASPENSIA 21 android-based interactive. The research used Borg & Gall model, when only up to stage 5 main product revision using expert validation test instruments and readability tests. The results of the study are (1) total validity score obtained 86.24%, very valid, where content feasibility aspect is 83.33%, language feasibility aspect is 87.63%, and presentation feasibility aspect is 87.77%, and (2) student readability test result 82.49%, very good category.